Auditoría financiera y su impacto en la razonabilidad de los estados financieros en la empresa rechafrut año 2020. - Torres Yunga, Mary Cecibel (2022)
The Financial Audit consists of the evaluation of operations, transactions and financial records, its purpose is to determine the economic and accounting management of a company and verify if the information presented is reliable, timely and useful. The present work was carried out in the company Rechafrut, which is in charge of the purchase and sale of rejected bananas, is located in the province of Los Ríos, Cantón Quevedo, via San Carlos Sector la Josefina 2 with tax domicile in the Cantón Quevedo . The main objective of the research is to develop a financial audit and its impact on the reasonableness of the financial statements in the Rechafrut company, is to give credibility to the reported financial position and business performance. The methodology used was field research, documented and exploratory, inductive, synthetic, deductive and analytical methods were used, in which they are methods used in data evidence for analysis, in order to discover new information. The collection of information was carried out through research techniques such as observation, interview and questionnaire, aimed at the personnel of the administrative, accounting and operational area, to obtain relevant information regarding the problem presented, which was subsequently analyzed through the processes of audit, the information obtained allowed us to examine the controls of the accounting procedures of the company, to later verify that the mechanisms used by the company for the accounting record are based on the IFRS for SMEs that have been adopted by the company so that it can be keep an adequate accounting record, and after carrying out the internal control of the expense account of the financial statements, the problem caused by not recording the expenses was determined, and the duPont analysis helped to know the average return on equity of the company and the direct relationship of the different accounts of the company.